Analisis Tingkat Pengetahuan Pekerja KAnalisis Tingkat Pengetahuan Pekerja Konveksi Tentang Postur Kerja Ergonomis onveksi Tentang Postur Kerja Ergonomis - Amran, Yuli; Adibatina, Ignace (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
Work in the field of garment demdans that workers carry out activities with a certain position to obtain good results. Low knowledge of ergonomic work postures causes many awkward positions when working, which has an impact on musculoskeletal disorders (MSDs). Preliminary studies conducted at the Small-scale Garment in Cipadu showed that most workers experienced complaints, especially in the neck dan back (70%). Therefore, it is necessary to analyze the level of knowledge of workers about ergonomic work posture in the field of small-scale garments as the basis for their countermeasures. The research with the Cross-Sectional study design made all workers in the small-scale garment Cipadu a population. A sample of 125 workers was taken using a simple rdanom sampling technique. Data were collected by the interview method using structured interview guidelines. Descriptive Statistical analysis is applied to describe the knowledge of workers. The Chi-Square test was chosen to look at the difference in the knowledge level of workers based on their individual characteristics. The results showed that only 66.4% of workers had a good knowledge of ergonomic work postures. Knowledge of ergonomic sitting work postures is least understood by workers. It can be concluded that knowledge of ergonomic work posture in workers still needs attention. Business owners are advised to partner with local authorities to socialize about ergonomic work postures to avoid the emergence of complaints of MSDs due to improper work posture. The process of providing education should be supported by the media for promoting occupational health dan safety to be more effective.